Upregulation of p21 activates the intrinsic apoptotic pathway in β-cells - Hernandez, Angelina M. (American Physiological Society, 2013)
Diabetes manifests from a loss in functional β-cell mass, which is regulated by a dynamic balance of various cellular processes, including β-cell growth, proliferation, and death as well as secretory function. The cell cycle machinery comprised of cyclins, kinases, and inhibitors regulates proliferation. However, their involvement during β-cell stress during the development of diabetes is not well understood. Interestingly, in a screen of multiple cell cycle inhibitors, p21 was dramatically upregulated in INS-1-derived 832/13 cells and rodent islets by two pharmacological inducers of β-cell stress, dexamethasone and thapsigargin. We hypothesized that β-cell stress upregulates p21 to activate the apoptotic pathway and suppress cell survival signaling. To this end, p21 was adenovirally overexpressed in pancreatic rat islets and 832/13 cells. As expected, p21 overexpression resulted in decreased [(3)H]thymidine incorporation. Flow cytometry analysis in p21-transduced 832/13 cells verified lower replication, as indicated by a decreased cell population in the S phase and a block in G(2)/M transition. The sub-G(0) cell population was higher with p21 overexpression and was attributable to apoptosis, as demonstrated by increased annexin-positive stained cells and cleaved caspase-3 protein. p21-mediated caspase-3 cleavage was inhibited by either overexpression of the antiapoptotic mitochondrial protein Bcl-2 or siRNA-mediated suppression of the proapoptotic proteins Bax and Bak. Therefore, an intact intrinsic apoptotic pathway is central for p21-mediated cell death. In summary, our findings indicate that β-cell apoptosis can be triggered by p21 during stress and is thus a potential target to inhibit for protection of functional β-cell mass.